Compressible, electrically conductive, fibre-like, three-dimensional PEDOT-based composite aerogels towards energy storage applications. (28th April 2016) - Zhao, Zhiheng; Moussa, Mahmoud; Shi, Ge; Meng, Qingshi; Wang, Ruoyu; Ma, Jun
Abstract: Three types of compressible, electrically conductive aerogels have been developed in this study using poly(3, 4-ethylenedioxythiophene) - polystyrene sulfonate (PEDOT-PSS). The crosslinking between PEDOT-PSS and polyethylene oxide (PEO) promoted the formation of welded fibre-like morphology, which was explained through the purpose-designed experiment and characterization. Single-walled carbon nanotubes (SWCNTs) were added to further improve the electrical conductivity and thus the electrochemical performance. The PEDOT-PSS/PEO/SWCNT aerogel was used to fabricate a flexible supercapacitor which exhibited a specific capacitance of 362 F g −1 at a scan rate of 20 mV s −1 ; it demonstrated an energy density of 67.7 Wh kg −1 and a power density of 13.5 kW kg −1 at 100 mV s −1 with 0–1.8 V potential window. When bent at 60°, the supercapacitor exhibited 318 F g −1 at 100 mV s −1 . The flexible supercapacitor showed a 94.6% retention after 5000 cycles at 5 A g −1 .